MANAS (MIND) AND MANOVIKARA (MENTAL DISORDER) IN AYURVEDA: A REVIEW (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is thought to be ‘The Science of Life’, and therefore the follow involves the care of physical and mental health of creature. Ayurveda isn’t solely restricted to body or physical symptoms however conjointly provide comprehensive data concerning mental and social health. Three factors are basically responsible for the origin of any kind of disease, these are Asatmaindriyartha Samyoga (excessive utilization or non-utilization or improper utilization of sense faculties), Prajnaparadha (Intellectual blasphemy) and Parinama (time). Balanced Doshas of mind regulates the emotion while disturbed Doshas of mind plays an important role in the pathogenesis of mental diseases. The increasing level of stress in today’s time gives a huge surge of Manovikara (mental disorder). In Ayurveda many references of Manas (mind) and treatment of Manovikara (mental disorder) are available which would be easy to understand and rewarding the field of treatment. Role of Swastavritta including Daivavyapasraya, Satwavajay, Naisthiki chikitsa and Yoga are very important in the management of Manovikara. In modern era we are at the grasp of Raja and Tama which are the root cause of mental disorder. So, it is necessary to understand the Manovikara (mental disorder), its causes, symptoms, prevention and management. Present article is a review article contains review of Manas (Mind) and Manovikara (Mental disorder) in Ayurveda.